2015
DOI: 10.12924/of2015.01010038
|View full text |Cite
|
Sign up to set email alerts
|

100% Organic Poultry Feed: Can Algae Replace Soybean Expeller in Organic Broiler Diets?

Abstract: Current EU regulations allow 5% of feed for organic poultry to come from non-organic production. This is due to concerns about a 100% organic diet meeting the requirements for specific amino acids such as methionine. This exception is due to end on 31st December 2017. While this may match consumer expectations, protein sourced from global organic production may have a negative impact on perceptions of organic poultry in other ways. Soybean is a commonly used ingredient in poultry feed but soybean production ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…It is reported that algae can be a good option for 100% organic poultry feed [47]. Neumann et al [36] reported that incorporation of Spirulina platensis at 21% and 17% in starter and grower phase, respectively was acceptable.…”
Section: Algaementioning
confidence: 99%
“…It is reported that algae can be a good option for 100% organic poultry feed [47]. Neumann et al [36] reported that incorporation of Spirulina platensis at 21% and 17% in starter and grower phase, respectively was acceptable.…”
Section: Algaementioning
confidence: 99%
“…Research has indicated that algae, such as brown, green, and red algae, possess nutritional value that could positively impact poultry production performance and meat quality [ 6 , 7 , 8 ]. Additionally, the potential of algae to replace soybean expeller in organic broiler diets has been investigated, suggesting that algae may maintain a desirable amino acid profile within the feed, thus promoting sustainability in poultry farming [ 9 ]. Moreover, feed enzymes have been identified as a means to enhance the nutritional value of algae and improve their suitability as partial replacements for conventional and unsustainable feed ingredients, such as corn [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Organic feeding in poultry is pricier but organic products are safer than conventional poultry products (Blair, 2008). Algae are used in organic poultry production, having high nutritional value (Gerrard et al, 2015). Two types of algae are widely used in poultry diet.…”
Section: Introductionmentioning
confidence: 99%